Perancangan Sistem Ujian Online Pada Rumah Pintar Bahasa Inggris Di Kampung Semanggi - Rahman, Taufik Nur; Rofiah, Ika Aliyatur R.; Dewanto, Dewanto; Setyawan, Bagus; Prasetio, Vio Jhondan; Sari, Mamik Usniyah; Muhandhis, Isnaini (Fakultas Teknik-Universitas Wijaya Putra, 2022)
Kampung Semanggi has an English Smart House that accommodates school-age students. This smart house provides English learning facilities. Based on the results of observations and interviews with the manager, they want a system to be made for online exam activities. This system is not only a necessity during a pandemic, but becomes a breakthrough learning method in the future. Based on this background, we held a service program for designing an online exam system for the English Smart House in Semanggi Village. System development is carried out with the waterfall stage. We use CodeIgniter framework, PHP language and MySQL database in system development. The results of using the online exam system, the exam process becomes easier, faster and more practical. This system helps teachers and students for the efficiency of the exam process